2019
DOI: 10.1111/scs.12635
|View full text |Cite
|
Sign up to set email alerts
|

Perception of nursing profession – focus group interview among applicants to nursing education

Abstract: Aims and objectives To explore nursing applicants’ perceptions of the nursing profession and to identify the factors influencing their perceptions. Background Perceptions guide the career choice in nursing and the retainment in the profession. Perceptions of nursing profession are said to be outdated and unrealistic among public. Therefore, more information is needed about the perceptions of nursing applicants. Design Exploratory qualitative design using focus group interviews. Methods Three focus group interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…Career choice theory indicates that parents, family and significant others play an important role in the career choice process of school pupils. [31,38] Our study found that participants' parents' education levels were associated with their intention. The findings of our study are consistent with previous research, [39] that family's high educational attainment, having a nurse in the family or relatives, influence of friends and guidance of teachers in career choices greatly impacted students' choice of nursing as a profession.…”
Section: Knowledge Attitude and Intentionmentioning
confidence: 64%
See 1 more Smart Citation
“…Career choice theory indicates that parents, family and significant others play an important role in the career choice process of school pupils. [31,38] Our study found that participants' parents' education levels were associated with their intention. The findings of our study are consistent with previous research, [39] that family's high educational attainment, having a nurse in the family or relatives, influence of friends and guidance of teachers in career choices greatly impacted students' choice of nursing as a profession.…”
Section: Knowledge Attitude and Intentionmentioning
confidence: 64%
“…[26] Nursing students at the beginning of their program had inaccurate knowledge about the profession and knew very little about the nursing profession. [27,31] Providing students with multifaceted opportunities to obtained accurate information about the multiple roles of nurses may contribute to the positive perceptions of a nursing profession in contemporary health care. [32] Overall, participants had a relatively negative attitude toward nursing profession, as reflected in the findings of the study that only one-third (38.0%) thought that nursing was a very interesting job and they felt comfortable with the conception of being a nurse.…”
Section: Knowledge Attitude and Intentionmentioning
confidence: 99%
“…Newly graduated nurses play an important role in delivering high‐quality patient care. Compared with the general population, facing the complicated and fast‐paced clinical environment means that newly graduated nurses must accurately identify urgent nursing tasks, which requires rapid decision‐making 49 . Even so, the prevalence of work procrastination among newly graduated nurses is concerning.…”
Section: Discussionmentioning
confidence: 99%
“…The genre remains popular in many parts of the world both in terms of global distribution and local production of shows (see for example, Bull, 2016;Gao, 2016;Riahi et al, 2020). Medical television drama is popular viewing among medical and nursing students (Glerean et al, 2019;Czarny et al, 2008). Medical television has been credited with encouraging applications to nursing education (Weaver et al, 2013) although it has also been mooted that unrealistic expectations of healthcare professions -whether derived from media, career counselling or friends and family -could contribute to attrition rates (Glerean et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Medical television drama is popular viewing among medical and nursing students (Glerean et al, 2019;Czarny et al, 2008). Medical television has been credited with encouraging applications to nursing education (Weaver et al, 2013) although it has also been mooted that unrealistic expectations of healthcare professions -whether derived from media, career counselling or friends and family -could contribute to attrition rates (Glerean et al, 2019). Television may also influence students' choice of specialism.…”
Section: Introductionmentioning
confidence: 99%